Mineralization of Organic Residues, Dynamics of Microbial Biomass and Enzyme Activities in an Aridisol and Alfisol Soil under Rain-Fed Dry Farming - Rehmat Ullah; Shehzada Munawar Mehdi; Khalid Saif Ullah Khan; Aftab Ahmed Sheikh; Endang Sulistyowati; Muhammad Saud (Badan Penerbitan Fakultas Pertanian (BPFP), 2018)
This study was planned with hypothesis to quantify mineralization rate of wheat and groundnut straw spiked in Kahuta and Guliana soil series. Results revealed that groundnut and wheat strawspiked soils had increased quantum of microbial biomass carbon (Cmic), biomass nitrogen (Nmic) and biomass phosphorous (Pmic) and activities of enzyme dehydrogenase (DHA) and alkaline phosphatase (APA) than un-amended soils. Initially, the contents of soil Cmic, Nmic, Pmic, DHA, and APA increased gradually during 2-14th days of incubation (DAI), again increased significantly at 28th DAI and then decreased slowly at 60th DAI in all treatments under both series. Hence, the addition of groundnut straw mineralized better than to other organic sources in both soil series. These results suggested that groundnut straw must be incorporated in soil one month before sowing of crop to enhance crop yield under rain-fed dry farming.Key words: Crop Residues, Microbial Biomass, Soil Enzymes, Aridisol, Alfisols